Randomized Trial of Transversus Abdominis Plane Block With Liposomal Bupivacaine After Cesarean Delivery With or Without Intrathecal Morphine. Issue 3 (24th September 2022) - Habib, A.S.; Nedeljkovic, S.S.; Horn, J.L.; Smiley, R.M.; Kett, A.G.; Vallejo, M.C.; Song, J.; Scranton, R.; Bao, X.
Abstract : ( J Clin Anesth . 2021;75:110527. doi: 10.1016/j.jclinane.2021.110527) Intrathecal morphine (ITM) is regularly used for analgesia following cesarean delivery (CD), although there is no standardized dose. Employed as part of a multimodal analgesia system, recommended ITM dosing ranges from 50 to 150 µg. Dose-dependent opioid-related adverse events including vomiting, nausea, pruritus, and respiratory depression call for investigation into alternate methods that provide effective analgesia with fewer opioid-related adverse events. Previous studies of transverse abdominis plane (TAP) block with long-acting liposomal bupivacaine (LB) combined with ITM suggest enhanced analgesia compared to LB TAP or ITM alone. The comparison of efficacy and safety of LB TAP block with or without ITM (LB and LB + ITM) versus ITM alone has not been previously undertaken. The adequacy of analgesia including pain scores and postsurgical opioid consumption was studied for the 3 intervention groups (LB and LB + ITM, vs. ITM) with noninferiority tested before superiority.